The anatomy of fake news a critical news literacy education - Higdon, Nolan (University of California Press, 2020)
"Since the 2016 U.S. presidential election, debates about fake news have appeared regularly in entertainment, politics, and news media. While many agree on the dangers associated with fake news, there is no consensus around the definition of the phenomenon, and its origins are loosely attributed to a variety of practices and technologies. Much of the discourse has focused on proposing solutions, with media literacy being one of the most frequently mentioned. However, Nolan Higdon argues that critical media literacy pedagogy will be unsuccessful without a comprehensive understanding of fake news. The Anatomy of Fake News offers the first examination of fake news for the purpose of creating effective critical news literacy. Higdon employs a critical-historical media ecosystems approach to identify the producers, themes, purposes, and influences of fake news and incorporates his findings into an invaluable fake news detection kit. This much-needed resource provides a rich history of fake news and a promising set of pedagogical strategies for mitigating its pernicious influence"--